2023
DOI: 10.1039/d2nr05382a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the nanostructure and molecular orientation of high molecular weight diketopyrrolopyrrole-based polymers for high-performance field-effect transistors

Abstract: As a versatile class of semiconductors, diketopyrrolopyrrole (DPP)-based conjugated polymers are well-suited for application of next-generation plastic electronics because of their excellent and tunable optoelectronic properties via rational design of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…[35,36] Li et al observed that the orientation of diketopyrrolopyrrole (DPP) polymers changes the electrical properties including transfer behavior and carrier mobility. [37] To control this orientation, DPP-based polymers typically modulate the packing texture through functional substituents such as side chains or conjugated segments. [38][39][40][41] Despite these attempts, DPP is not easily electrochemically doped by anion dopants, resulting in short-term plasticity (STP) or short retention time, which limits its use in artificial synapse implementation.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] Li et al observed that the orientation of diketopyrrolopyrrole (DPP) polymers changes the electrical properties including transfer behavior and carrier mobility. [37] To control this orientation, DPP-based polymers typically modulate the packing texture through functional substituents such as side chains or conjugated segments. [38][39][40][41] Despite these attempts, DPP is not easily electrochemically doped by anion dopants, resulting in short-term plasticity (STP) or short retention time, which limits its use in artificial synapse implementation.…”
Section: Introductionmentioning
confidence: 99%
“…1,13−15 However, the strong aggregation property of DPP-based polymers can lower the solubility of the polymer in organic solvents and limit the types of available solvents or solution processes in fabricating devices. 11,16,17 In this study, we designed a new DPP-based polymer with long and branched alkyl side chains to improve the solubility of DPP polymers. The new DPP-based polymer, poly[2,5-bis(7decylnonadecyl)pyrrolo [3,4-c]pyrrole-1,4-(2H,5H)-dione-2,2′-dyl-alt-thieno[3,2,-b]thiophen-2,5-dyl] (P29DPP-TT), have DPP moieties as electron-deficient cores, electron-rich thienothiophene units, and thiophenes as bridges (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Diketopyrrolopyrrole (DPP)-based polymers have emerged as one of the most useful candidates to make applications in electronic devices such as organic field-effect transistors (OFETs) and organic photovoltaics (OPVs). The DPP-conjugated moiety has a planar and rigid structure and is able to form hydrogen bonds, which facilitate molecular assembly and promote crystallization. , However, the strong aggregation property of DPP-based polymers can lower the solubility of the polymer in organic solvents and limit the types of available solvents or solution processes in fabricating devices. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggested that the molecular effects can influence polymer aggregation in materials, and the photoactive layer morphology has profound effects on the photovoltaic properties and stability of PSCs. Specifically, the crystallinity of conjugated polymer films determines charge transport in the vertical direction. Moreover, solution processing methodologies can effectively control the polymer chain packing structure and subsequent film morphology.…”
Section: Introductionmentioning
confidence: 99%
“…8 In general, PSC photovoltaic performance is strongly dependent on the chemical and condensed-state structures of conjugated polymers, photovoltaic active layer morphology, and device structure, upon which major efforts have been focused to date. 9−12 Previous reports suggested that the molecular effects can influence polymer aggregation in materials, 13 and the photoactive layer morphology has profound effects on the photovoltaic properties and stability of PSCs. 14−18 Specifically, the crystallinity of conjugated polymer films determines charge transport in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%